2013
DOI: 10.1136/annrheumdis-2012-202810
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ needs and expectations with regard to rheumatology nursing care: results of multicentre focus group interviews

Abstract: Patients with CIA mentioned that many problems have to be addressed when one is faced with having a rheumatic disease. The focus group interviews yielded valuable information about the care these patients need and expect. This information will direct future research with regard to rheumatology nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 29 publications
2
70
0
Order By: Relevance
“…Patients needed information from an expert about diagnosis, symptoms, treatment options, side‐effects and possible interaction effects and instruction on alleviating symptoms themselves . Support should be available shortly after symptoms arise or when there are problems with medication . In some studies, patients appreciated information about spiritual matters and complementary therapy .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients needed information from an expert about diagnosis, symptoms, treatment options, side‐effects and possible interaction effects and instruction on alleviating symptoms themselves . Support should be available shortly after symptoms arise or when there are problems with medication . In some studies, patients appreciated information about spiritual matters and complementary therapy .…”
Section: Resultsmentioning
confidence: 99%
“…Professionals also helped evaluate internet information, a role attributed to relatives in another study . Information about health‐care facilities was needed from professionals . Some studies pointed out that providing information to relatives is important as well .…”
Section: Resultsmentioning
confidence: 99%
“…In The Netherlands and the Scandinavian countries NLC is well established,14–16 18 19 while in other countries it is in its infancy 20–22. The European League Against Rheumatism (EULAR) has recently published recommendations for the role of the nurse in the management of inflammatory arthritis, in order to enable a homogenisation of rheumatology nursing care across Europe 23.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent research found that patients wanted emotional support from a professional, regarding it as beneficial to share problems with someone outside of their social environment 23. There is some evidence that different psychological factors affect coping and adaptation at different stages, making disease duration and disease trajectory (e.g.…”
Section: Introductionmentioning
confidence: 99%